Hydrogeochemical Characterization and Qualitative Assessment of Groundwater in Jampali Coal Mining Area, Chhattisgarh, India - Ahmed S.I.; Sonkar A.K.; Kishore N.; Varshney R.; Jhariya D. (My University, 2025)
Groundwater is an essential natural source of water for human beings. Anthropogenic activities and excessive exploitation cause groundwater contamination. The research proceeds around the Jampali opencast coal mine of Raigarh district, Chhattisgarh, India. Twenty-eight groundwater samples were collected in November 2018, and twelve physicochemical parameters were analysed from groundwater samples. The sequence of ionic load of significant cations was Na+ > Ca2+ > K+ > Mg2+, whereas the anions were HCO3− > Cl− > SO42− > NO3− > F−. Water facies analysis shows that most groundwater samples belong to CaMg-HCO3 and Ca–Mg–Cl–SO4. The Gibbs plot shows that cation and anion accumulation in the study area was caused by rock dominance and evaporation crystallisation. Strong positive correlations were noticed between TDS–EC, TDS–Cl−, TDS–SO42−, TDS–K+, EC–SO42−, EC–Cl−, EC–K+, Ca2+–HCO3−, Mg2+–Na+, Mg2+–SO42−, Na+–SO42−, K+–Cl−, and Mg2+–F−. Groundwater falls under excellent (79%), good (18%), and poor water classification, according to the water quality index. The spatial distribution map showed the general trend of increase in physicochemical parameters. Nitrate (GW-8) and F− (GW-4 and GW-11) exceed the permissible limit. Clusters 1, 2, and 3, according to WQI, have a maximum (78%), moderate (18%), and least number of sampling stations, respectively. The groundwater around the Jampali coal mine is suitable for drinking and other uses with some treatment. © 2022, The Institution of Engineers (India).